THE ANALYSIS OF ISLAMIC CHARACTERS IN FORMINGCARING BEHAVIOR OF NURSING STUDENT - Addiarto, Widya; Nusantara, Ana Fitria; Salam, Ainul Yaqin (Jurnal Keperawatan Respati Yogyakarta, 2021)
Nurse is the type of health workers who interacts most with clients so that their services become one of the benchmarks for the success of health services in the hospital. The ability to pay attention to others, intellectual, technical and interpersonal skills of nurses are reflected in their caring behavior when providing nursing care. Nurse's caring behavior is closely related to the Islamic character. Islam itself is seen not only as a religion but also as a way of life that guides people in peace and compassion. The main principle of caring from an Islamic perspective is based on God's revelations and those who practice caring for others will receive many blessings. Muslims believe that the teachings of their religion carry all aspects of life and they seek to keep God at the center of consciousness, intention and action. The research objective was to determine the relationship between Islamic characters and the caring behavior of nursing students. The study used a descriptive analytic cross sectional design and analyzed using the Spearman Rank test with 93 respondents. The results showed that the majority of respondents had good caring behavior, with the conclusion that there was a significant relationship between Islamic characters and student caring behavior. Religion and the environment can be important factors in the formation of Islamic character, which is shown by the nurse's caring behavior towards clients. Keywords: Caring Behavior; Islamic Character; Nurse